Phenomenon Of SMEs (Small and Medium Enterprises) and Community Mindset - Sayyida, Sayyida; Alwiyah, Alwiyah (Pandawan, 2020)
Small and medium enterprises (SMEs) are the core of modern economic life that is very important for economic development in Indonesia, so the government seeks to empower SMEs. Bluto - Sumenep has many SMEs but is difficult to develop. This study aims to analyze the phenomenon of SMEs in Bluto related to the success of their business in relation to education, skills and funds. Questionnaires were used to obtain data from 100 entrepreneurs. The result of correlation analysis shows that there is no relationship between business success with education, skill and fund. This result proves the unique phenomenon of the mindset of the Bluto people who consider that